THE INFLUENCE OF ONLINE LEARNING MEDIA EFFECTIVENESS, SELF-EFFICIENCY AND LEARNING MOTIVATION ON STUDENTS' ECONOMIC LEARNING OUTCOMES AT SMA NEGERI 38 JAKARTA IN THE ERA OF PANDEMIC COVID- 19 - Robiyansah, Muchamad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the influence of online learning media, learning motivation self-efficacy on student learning outcomes based on valid and reliable data. The research was conducted at SMA Negeri 38 Jakarta. The method used is a survey method. The affordable population in this study were all students of class XI majoring in Social Sciences, totaling 120 students. Sampling using saturated sampling technique, namely the entire population sampled in this study. The instrument used to obtain data on variables X1 (Online Learning Media Effectiveness), X2 (Self Efficacy) and variables Y (Learning Motivation) were measured using a Likert scale. As for the variable Z (Student Learning Outcomes) using data on student test scores given by SMA Negeri 38 Jakarta teachers. The data analysis techniques used is the requirement analysis test, hypothesis test, description analysis and path analysis. Test requirements analysis performed shows the results that are normally distributed and linear data. The results of this study indicate that the effectiveness of online learning media has no effect on learning outcomes, self-efficacy has no effect on learning outcomes, learning motivation has a significant positive effect on learning outcomes, the effectiveness of online learning media has a significant positive effect on learning motivation, self-efficacy has a significant positive effect on motivation. Another thing can be concluded in this study that learning motivation can mediate the effectiveness of online learning media and self-efficacy variables on learning outcomes.